2001
DOI: 10.1074/jbc.m010416200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of a Novel Mammalian Lectin, Ym1, Suggests a Saccharide Binding Site

Abstract: Ym1, a secretory protein synthesized by activated murine peritoneal macrophages, is a novel mammalian lectin with a binding specificity to GlcN. Lectins are responsible for carbohydrate recognition and for mediating cell-cell and cell-extracellular matrix interactions in microbes, plants, and animals. Glycosaminoglycan heparin/heparan sulfate binding ability was also detected in Ym1. We report here the three-dimensional structure of Ym1 at 2.5-Å resolution by x-ray crystallography. The crystal structure of Ym1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 63 publications
1
79
0
Order By: Relevance
“…Surface plasmon resonance has demonstrated the binding of Ym1 to GlcN oligomers (chitobiose, chitotriose, and chitotetraose), and heparin sulfate has also been suggested as a candidate ligand (21). Analysis of the crystal structure of Ym1 has also proposed a saccharide-binding site (38). Interestingly, other homologous proteins have been associated with tissue remodeling, a function that may be related to carbohydrate interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Surface plasmon resonance has demonstrated the binding of Ym1 to GlcN oligomers (chitobiose, chitotriose, and chitotetraose), and heparin sulfate has also been suggested as a candidate ligand (21). Analysis of the crystal structure of Ym1 has also proposed a saccharide-binding site (38). Interestingly, other homologous proteins have been associated with tissue remodeling, a function that may be related to carbohydrate interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Ym1 has been associated with alternatively activated macrophages and has weakly active eosinophil recruiting activity (38,52). Ym1 binds saccharides with a free amine group, including n-glucosamine and their oligosaccharides, as well as heparin, suggesting a role in binding to both extracellular matrix and parasite eggs (8,49). It has therefore been suggested that Ym1 is involved in tissue remodeling involving changes in the extracellular matrix (52).…”
Section: Discussionmentioning
confidence: 99%
“…These include YKL-40 (chitinase 3-like-1), YKL-39 (chitinase 3-like-2), Ym1/2 (chitinase 3-like-3/4), oviduct-specific glycoprotein and stabilin-1-interacting chitinaselike protein [11][12][13][14][15][16][17]. YKL-40 (also termed HC-gp39 or Chi3l1) was found to be secreted, along with chitotriosidase, from activated human macrophages and it was later detected in the culture supernatant of chondrocytes, synovial cells and osteoblasts [2,11].…”
Section: Introductionmentioning
confidence: 99%